2015
DOI: 10.1159/000442577
|View full text |Cite
|
Sign up to set email alerts
|

Branch Atheromatous Disease: A Clinically Meaningful, Yet Unproven Concept

Abstract: Background: In 1989, Louis Caplan first used the term branch atheromatous disease (BAD) to describe an occlusion or stenosis at the origin of a deep penetrating artery of the brain, associated with a microatheroma or a junctional plaque, and leading to an internal capsule or pontine small infarct. BAD remained an understudied concept for decades. In recent years, the increasing diffusion of high-resolution magnetic resonance imaging (HRMRI) techniques brought new attention to the BAD debate. We have reviewed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
125
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 51 publications
4
125
1
3
Order By: Relevance
“…Consistent with the pathological and clinical evidence for atherosclerotic large-artery disease involvement in BABAD [3, 4, 18], we also found a high frequency of severe large artery atherosclerotic stenosis (ICA and MCA) in BABAD patients. Considering WMH is a commonly used SVD marker [713], the vascular risk factor-adjusted finding of greater WMH severity in the BABAD group compared to the NS and LAA groups implies that SVD is also involvement in the pathophysiology of BABAD.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the pathological and clinical evidence for atherosclerotic large-artery disease involvement in BABAD [3, 4, 18], we also found a high frequency of severe large artery atherosclerotic stenosis (ICA and MCA) in BABAD patients. Considering WMH is a commonly used SVD marker [713], the vascular risk factor-adjusted finding of greater WMH severity in the BABAD group compared to the NS and LAA groups implies that SVD is also involvement in the pathophysiology of BABAD.…”
Section: Discussionsupporting
confidence: 90%
“…The definition of larger size has the same meaning as branch atheromatous disease (BAD). Although the term BAD was originally created based on pathological findings [15], studies based on neuroimaging have increased in accordance with the progress of MRI [16]. In many studies, BAD was defined as a diameter > 1.5 mm and/or the appearance of a lesion on > 3 consecutive slices on MRI [7,17].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding obesity, although a significant difference was shown in multivariate analysis, perhaps due to the smaller sample size compared to other factors, obesity may be less likely to be a direct factor involved in the poor BAD prognosis. Moreover, it is interesting to note that results from a recent review by Inzitari and colleagues [8] showed no consistent associated vascular risk factors or predictors of progression for BAD. Finally, reports on the use of intravenous medication have been controversial.…”
Section: Discussionmentioning
confidence: 99%
“…1a, b). Historically, pathological studies have been used to identify mechanisms of stroke; however, in recent years, high-resolution and high-field magnetic resonance imaging (MRI) have been used to further delineate the intracranial vessel wall morphology in small-vessel occlusive disease [7,8]. However, currently there is no corresponding cerebrovascular disorder classification in the National Institute of Neurological Disorders and Stroke (NINDS) [9] or diagnostic criteria in the Trial of Org 10172 in Acute Stroke Treatment (TOAST) [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation